Effects of maltene on the attributes of reclaimed asphalt pavement: Performance optimisation - Al-Saffar, Zaid Hazim; Haryati, Yaacob; Mohd Khairul Idham, Mohd Satar; Putra Jaya, Ramadhansyah; Norazah, Basa; Radeef, Hassanain Radhi; Norhidayah, Abdul Hassan (Elsevier, 2021)
The asphalt mixtures using elevated percentages of the reclaimed asphalt pavement (RAP) are of significant interest due to its ability to address environmental issues and reduce cost of asphalt. However, utilising elevated RAP content is associated with several disadvantages. Hence, this study explores the potential application of maltene as a rejuvenator to improve the output of asphalt mixtures incorporating RAP binder. The contents of maltene were optimised according to several parameters, namely penetration, softening point, ductility, and viscosity tests. Thereafter, the specimens containing an optimum maltene percentage were assessed using maltene-to-asphaltene ratio, storage stability, Dynamic Shear Rheometer (DSR), Bending Beam Rheometer (BBR), Fourier Transform Infrared (FTIR) spectroscopy and Thermogravimetric Analysis (TGA) measurements. Subsequently, the mechanical characteristics of asphalt mixtures were analysed using Marshall Stability, moisture damage, resilient modulus (MR), and Cantabro loss tests. The results demonstrated that 8% and 16% of maltene restored the physical properties of 30% and 50% of RAP binder, respectively. In addition, the workability was improved due to the reduction of viscosity, while maltene-rejuvenator managed to compensate the light components of RAP binder that were lost during the lifespan. As a result, the high- and low-temperature performance of RAP binder were restored approximately to that of virgin asphalt (VA). The oxygenated indices of RAP binder were effectively abated by blending with maltene. The TGA exhibited that the thermal stability of rejuvenated asphalts was close to VA. Accordingly, the mechanical characteristics of rejuvenated mixtures were improved compared to the VA mixture. Therefore, the maltene with a suitable dose is recommended to rejuvenate the RAP binder, and reuse it in the pavement construction.